Buddhist Management Strategies to Improve the Quality of Education in Small Schools under Mahasarakham Primary Service Area Office - Nammungkhun, Chanai; Suwanseantavee, Vimonporn; Muiethaisong, Suthep (Dhammathas Academic Journal, 2024)
The purposes of this research were 1) to study Conceptual framework Buddhist management strategies to improve the quality of education in small schools, 2) to create Buddhist management strategies to improve the quality of education in small schools, 3) to confirm Buddhist management strategies to improve the quality of education in small schools. The sample group used in the research included of 248 school administrators and teachers. The instruments used in this research were questionnaires, interviews, and strategy assessments. The questionnaire had a 5 level rating scale with content validity between 0.80-1.00. The confidence value was .97. Assessment of suitability and feasibility the content accuracy was between 0.80-1.00 and the reliability was .90. The statistic used in data analysis included of frequency, percentage, mean, standard deviation, and techniques for prioritizing needs PNI modified. The results revealed that: 1. Concepts, theories, documents and related research results, and formulated a conceptual framework for research in 5 aspects, namely 1) Organizational competency, 2) Academic leadership, 3) Learning process organization, 4) School atmosphere, 5) Community participation. 2. Buddhist management strategies to improve the quality of education in small schools, it consisted of 1) Organizing the learning process, 6 measures and 6 indicators of success. 2) School atmosphere and environment, had 10 measures, and 10 indicators of success. 3) Community participation, had 9 measures, and nine indicators of success, 4), Academic leadership, had 7 measures, and 7 indicators of success. 5), Organizational competency, had 4 measures, and 4 indicators of success. 3. Evaluation of suitability and feasibility to confirm Buddhist management strategies to raise the quality of education in small schools found that every strategy, every measure was appropriate and feasible and passed the specified criteria at the highest level. Can be used effectively in small schools and other agencies.